2019
DOI: 10.1177/2151459319835109
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Frailty on Short-Term Outcomes After Elective Hip and Knee Arthroplasty in Older Adults: A Systematic Review

Abstract: Introduction: This systematic literature review evaluates (1) frailty in older adults as a risk factor for short-term adverse events and suboptimal clinical outcomes after total joint arthroplasty and (2) interventions to improve arthroplasty outcomes in these frail patients. Methods: PubMed, EMBASE, Cochrane Register of Controlled Trials, SCOPUS, AgeLine, and Web of Science were searched from database inception to November 22, 2017; gray literature and references were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…Although total hip arthroplasty is one of the most common orthopedic procedures in older adults, studies of the frailty and THA results are limited to the traditional outcomes [7]. In this study, we analyzed the complex impact of frailty on the outcomes of THA focusing on patient-centered outcome measures such as long-term function (WOMAC, HHS), pain sensations (VAS), and satisfaction (HKAAS).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although total hip arthroplasty is one of the most common orthopedic procedures in older adults, studies of the frailty and THA results are limited to the traditional outcomes [7]. In this study, we analyzed the complex impact of frailty on the outcomes of THA focusing on patient-centered outcome measures such as long-term function (WOMAC, HHS), pain sensations (VAS), and satisfaction (HKAAS).…”
Section: Discussionmentioning
confidence: 99%
“…Schmucker et al [7] performed a systematic review of the impact of frailty on outcomes after THA and TKA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that functional indicators such as TUG and sit-to-stand test are useful in predicting postoperative recovery [7-10, 14, 19-22]. In addition, with the increasing age of patients who undergo artificial joint replacement, the importance of evaluating physical frailty has been reported in recent years [23]. Currently, various methods are used to assess physical frailty, but due to its simplicity and predictive capability, gait speed has become a core strategy to evaluate physical frailty.…”
Section: Discussionmentioning
confidence: 99%